Intellectual Property Rights in the Growth of MSMEs Ecosystem in Indonesia - Jaman, Ujang Badru (Yayasan Ilomata, 2024)
This study explores the pivotal role of Intellectual Property Rights (IPR) in shaping the growth dynamics of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Utilizing Structural Equation Modelling with Partial Least Squares (SEM-PLS), the research analyzes the relationships between intellectual property awareness, utilization, innovation, and competitiveness among 110 MSMEs. The findings highlight a significant positive relationship between intellectual property awareness and utilization, a strong link between intellectual property protection and innovation, and a notable impact on competitiveness. Furthermore, the study identifies intellectual property as a partial mediator, providing a nuanced understanding of its role in MSME growth. Practical implications include the need for educational initiatives to enhance IPR awareness, simplified registration processes, and strategic intellectual property management to foster innovation and competitiveness. These insights are crucial for policymakers and MSMEs striving for sustainable growth and a competitive edge in the global market.